Le processus incapacitant au cours du vieillissement : rôle de l’exercice/activité physique - Philipe de Souto Barreto; Anne-Marie Ferrandez (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Aging is a phenomenon of increased importance in contemporaneous societies. Although it is well established that physical exercise/activity contributes to maintain functional fitness at optimal levels, physical inactivity is a largely prevalent behaviour among elderly people, thus facilitating the disablement process. The purpose of this review is to studyphysiological and functional declines during aging. This article also tries to clarify the role played by physical exercise/activity in avoiding or delaying those declines, and in reverting or diminishing their negative impacts on older adults’ health. The influences of both disablement process main components (frailty, disability, and dependence) and of physical exercise/activity on functional fitness are examined. Concerning the relationships between physical exercise/activity and disablement process, some inconsistencies arise among articles, making difficult to compare them and to draw conclusions. The definitions of frailty, as well as the ways to measure physical exercise/activity, constitute the main inconsistencies among studies. However, most of the researches show that a regular practice of physical exercise/activity decreases the age-related declines in both physiological status and functional fitness. Then, exercising regularly can contribute to maintain independence in older adults by reducing the negative effects of the disablement process.